Antifungal activity of polygodial isolated from polygonum acuminatum and of the biotransformation product - Derita, Marcos Gabriel (2011)
The current interest in the development of new antifungal agents can partially be due to the dramatic rise in the number of patients with suppression of their immune system. Otherwise, the emergence of fungal resistance to available antifungal agents, leads to an increasing need for new and effective structures.(1) Polygonum acuminatum (Polygonaceae) is used to heal infected wounds in the traditional Argentinean medicine.(2) This study was carried out to evaluate the antifungal properties of this plant to give support to its ethnopharmacological use, and to isolate the compound(s) responsible for its activity. In addition, a fungal biotransformation of the main compound was performed.